SERS-based sandwich bioassay protocol of miRNA-21 using Au@Ag core–shell nanoparticles and a Ag/TiO2 nanowires substrate. Issue 23 (28th May 2019) - Peng, Le; Zhou, Jun; Liang, Zhaoheng; Zhang, Yaping; Petti, Lucia; Jiang, Tao; Gu, Chenjie; Yang, Danting; Mormile, Pasqule
Abstract : Based on surface-enhanced Raman scattering (SERS) technology, Au@Ag@4MBA@5′-NH2 -ssDNA probes and a Ag/TiO2 @3′-NH2 -ssDNA substrate were prepared and constructed into a sandwich structure to develop a high sensitivity bioassay of miRNA-21. Abstract : Based on surface-enhanced Raman scattering (SERS) technology, Au@Ag@4MBA@5′-NH2 -ssDNA probes and a Ag/TiO2 @3′-NH2 -ssDNA substrate were prepared and constructed into a sandwich structure to develop a high sensitivity bioassay of miRNA-21. The Au@Ag@4MBA@5′-NH2 -ssDNA probes were prepared by immobilizing 5′-NH2 -ssDNA onto the surfaces of 4MBA-labelled Au@Ag core–shell nanoparticles, and the Ag/TiO2 @3′-NH2 -ssDNA substrate was prepared by immobilizing 3′-NH2 -ssDNA on the surface of Ag/TiO2 nanowires SERS-active substrates. The experimental results showed that the SERS-based sandwich bioassay of miRNA-21 presented a low limit of detection of 0.75 fM and a broad dynamic range from 1.0 fM to 1.0 nM. Also, the test data for the SERS-based sandwich bioassay were not only consistent with that of the real-time fluorescence quantitative polynucleotide chain reaction (RT-qPCR) method but also displayed higher detection sensitivity. It was shown that the SERS-based sandwich bioassay of miRNA-21 has importance for use in potential applications involving diagnosing clinical cancer patients.